The Relationship Between Hospitality Implementation and Individual Characteristics with Patient Satisfaction Regarding Health Services at Community Health Centers Matraman, East Jakarta in 2025 - Nurmiati; Budiharto Budiharto; Tri Suratmi (International Journal of Health and Pharmaceutical (IJHP), 2026)
Hospitality in health services encompasses friendliness, effective communication, empathy, and facility comfort. The policy on Hospitality in health services in DKI Jakarta Province is based on the Decree of the Head of the Jakarta Health Office No. 407 of 2021 concerning Health Service Guidelines that prioritize hospitality. The implementation of this policy requires evaluation to determine the achievement of its objectives. This study aimed to analyze the implementation of the Hospitality policy and individual characteristics in relation to patient satisfaction at Matraman Community Health Center, East Jakarta, in 2025. The research method employed was descriptive analytic with a quantitative approach and cross-sectional design. A total sample of 100 respondents was drawn from the population using the Slovin formula, with inclusion criteria being respondents aged ≥16 years, male or female, and patients or individuals utilizing health services at Matraman Community Health Center. Data were collected through a questionnaire that had undergone validity and reliability testing. Data analysis included univariate, bivariate, and multivariate tests. The results showed that patient satisfaction levels were generally high, with the majority reporting “satisfied” and some “very satisfied.” Bivariate analysis indicated significant relationships between friendliness (p = 0.0001; OR = 40.289), communication (p = 0.0001; OR = 19.167), empathy (p = 0.0001; OR = 43.714), and facility comfort (p = 0.0001; OR = 12.500) with patient satisfaction. Individual characteristics showed no significant relationship. Multivariate analysis identified empathy (p = 0.0001; OR = 13.850) as the dominant factor, followed by friendliness (p = 0.002; OR = 11.075). In conclusion, patient satisfaction at Matraman Community Health Center is primarily associated with staff empathy and friendliness.